Effect of Coffee Grounds as Compost on The Growth of Vorstenlanden Tobacco - Arbby Bonaventura; Anna Kusumawati (Journal of Global Sustainable Agriculture, 2022)
Tobacco is an important commodity in Indonesia because the tobacco industry makes a significant contribution to the Indonesian economy. Tobacco plants need nutrients to grow optimally. One source of nutrients for soil media is compost made from coffee grounds. These coffee grounds are often found as waste from the many coffee shops in Yogyakarta. The purpose of this study was to determine the effect of organic fertilizer made from coffee grounds on soil fertility and the growth of Vorstenlanden tobacco plants on different compositions of growing media. This research was carried out using a non-factorial completely randomized design with 5 levels A0 (Without giving coffee grounds compost), A1 (53 gr compost), A2 (105 gr compost), and A3 (158 gr compost), A4 (210 gr compost). The results showed that the administration of coffee grounds compost with the lowest amount gave the highest growth pattern compared to the treatment with the high amount of coffee grounds compost, and the application of coffee grounds compost did not show a significant increase compared to the treatment with coffee grounds compost. Compost of coffee grounds fermented for 2 weeks should not be applied to Vorstenlanden tobacco plants.